GPR 3D root mapping system - Lee, Christy Yingxuan (Nanyang Technological University, 2023)
National Parks Board (NParks) of Singapore is responsible for the forestry of the island which naturally constitutes monitoring and managing the structural development and health conditions of the trees and its roots. This paves the way for the construction of a well conserved and sustainable biodiverse ecosystem and climate, as well as ensure that our greenery lives healthily alongside our busy urban structures. Available methods of tree assessments are abundant but are often intrusive, Ground Penetrating Radar (GPR) emerges as a promising non-destructive testing (NDT) method among others such as ultrasound tomography, or infrared thermography in large-scale forestry applications. In this project, GPR and its processing techniques are investigated to engineer a system that 3D maps the root system architecture of desired tree populated landscapes to allow for the ease of monitoring the health conditions of trees. This includes the evaluation of construction of a GPR vehicle and its automation and processing features, leading into interfaces used to monitor this system and its results. This system should eventually work as a prototype to assist its intended operators at Nparks to assess tree root health based on crucial parameters such as relative permittivity.